2014
DOI: 10.5999/aps.2014.41.4.387
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ischial Pressure Sores with Both Profunda Femoris Artery Perforator Flaps and Muscle Flaps

Abstract: BackgroundReconstruction of ischial pressure sore defects is challenging due to extensive bursas and high recurrence rates. In this study, we simultaneously applied a muscle flap that covered the exposed ischium and large bursa with sufficient muscular volume and a profunda femoris artery perforator fasciocutaneous flap for the management of ischial pressure sores.MethodsWe retrospectively analyzed data from 14 patients (16 ischial sores) whose ischial defects had been reconstructed using both a profunda femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Thus, the early clinical applications of this flap were for ischial pressure sore reconstruction. [12][13][14][15] Later, Allen et al reported the first use of the profunda artery perforator flap for breast reconstruction. 16 Initially, the flap harvesting was performed in the prone position, and a supine "frog-leg" position was later adopted to eliminate the need for repositioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the early clinical applications of this flap were for ischial pressure sore reconstruction. [12][13][14][15] Later, Allen et al reported the first use of the profunda artery perforator flap for breast reconstruction. 16 Initially, the flap harvesting was performed in the prone position, and a supine "frog-leg" position was later adopted to eliminate the need for repositioning.…”
Section: Discussionmentioning
confidence: 99%
“…12 The clinical application of skin flaps from the posterior medial thigh region was most often used for ischial pressure sore reconstruction. [12][13][14][15] Allen et al reported the profunda artery perforator flap for autologous breast reconstruction when abdominal tissue was not available and, recently, the posterior medial thigh flap has been described as a free flap for breast reconstruction. [16][17][18] To our knowledge, there is a paucity of data describing the clinical application of this flap for head and neck reconstruction.…”
mentioning
confidence: 99%
“…Homma et al described using this flap as a proximally based pedicle flap to treat ischial pressure and used skin paddles ranging from 11 to 23 cm × 5 to 6 cm with favorable results in 10 patients. It was also demonstrated that closure of both the ischial defect and donor site could be achieved simultaneously . This option can be modified using the propeller concept for flap transposition as introduced by Hallock reported in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fasciocutaneous flaps (e.g. anterolateral thigh perforator flap, gluteal perforator flap, gracilis perforator flap, and profunda femoris perforator flap) have good blood supply, sufficient bulk and allow for muscular function preservation . However, they may become less useful when filling of a wound with significant depth is required.…”
Section: Discussionmentioning
confidence: 99%